HyLogger-3, a visible to shortwave and thermal infrared reflectance spectrometer system for drill core logging: functional description. Issue 8 (16th November 2016) - Schodlok, M. C.; Whitbourn, L.; Huntington, J.; Mason, P.; Green, A.; Berman, M.; Coward, D.; Connor, P.; Wright, W.; Jolivet, M.; Martinez, R.
ABSTRACT: Australian Geological Surveys are the custodians of a major national asset in the form of historically drilled and archived drill cores of the top few kilometres of the continent acquired by government agencies and companies over many decades. The AuScope National Virtual Core Library (NVCL) component of the AuScope Earth Model comprises geological/rock samples, technology, people and database/delivery infrastructure located in six nationally distributed nodes and is aimed at extracting additional value from this asset. The technology components of the NVCL comprise an integrated suite of hardware (HyLogger-3) and software (TSG-Core) systems for the imaging and hyperspectral characterisation of drill cores in their original core trays and the interpretation of their contained oxide, carbonate, hydrous and anhydrous silicate mineralogy. The HyLogger-3 includes state-of-the-art Fourier Transform Spectrometers that continuously measure calibrated spectral reflectance from nominal 10 by 18 mm fields of view. These spectra are in turn passed through a series of automatic and semi-automatic pre-processing and mineralogical unmixing algorithms. These, along with numerous other tools in TSG-Core, output a variety of mineralogical and image products for use by scientists in many branches of the earth sciences. This paper provides a functional overview of the HyLogging hardware and software tools available in each of Australia's Geological Surveys.